The making of Fantastic Mr. Fox - Anderson, Wes; Specter, Michael; Lewis, Ray (Rizzoli, 2009)
Originally published in 1970, Roald Dahl's Fantastic Mr. Fox tells the story of the Fox Family. After twelve years, the Fox Family's quiet home life proves too much for Mr. Fox's natural animal instincts. When his young nephew arrives, Mr. Fox slips back into his old ways as a smart bird thief and, in doing so, endangers not only his beloved family, but the whole animal community as well.